Recent Referees (Journal of Political Economy, 2022)
Previous articleNext article FreeRecent RefereesPDFPDF PLUSFull Text Add to favoritesDownload CitationTrack CitationsPermissionsReprints Share onFacebookTwitterLinked InRedditEmailQR Code SectionsMoreJournal of Political Economy acknowledges the assistance of:Jérôme AddaS. Nageeb AliHunt AllcottFranklin AllenMilena AlmagroManuel AmadorMartin AndresenAndrés Aradillas-LópezDavid ArgenteEnghin AtalayAna BabusRavi BansalNathaniel Baum-SnowSamuel BazziAriel BenYishayAndrew BernardAnmol BhandariKelly BishopChristopher BlattmanLaura BlattnerLuis BraidoNick BuchholzJing CaiColin CamererDavide CantoniXu ChengLesley ChiouJonathan ChiuTimothy ChristensenDamon ClarkHarold ColeDecio CovielloMartin William CrippsMichael CunaMaarten De RidderRahul DebMathias DewatripontSebastian Di TellaChris EdmondMartin EichenbaumPaul EllicksonHuberto EnnisMax FarrellBruno FermanJesús Fernández-VillaverdeMartin FiszbeinChristopher FlinnPatrick FrancoisEric FrenchGiovanni GallipoliNicolae GârleanuGeorge-Levi GayleMaitreesh GhatakElisa GiannoneAndy GloverDaniel GottliebSteven HaiderJames HamiltonStephen HansenGlenn HarrisonUlrich HegeTakeo HoshiChih-sheng HsiehKilian HuberGur HubermanJohn Eric HumphriesGaston IllanesAlex ImasYannis IoannidesJessica JeffersBruno JullienKei KawaiAmir KermaniAyumu KikkawaMarieke KleemansMichael KoelleRalph KoijenAnton KorinekAndreas Ravndal KostølIlan KremerAstrid KunzeDanial LashkariLihua LeiChe-Yuan LiangMikael LindahlJeremy LiseIgor LivshitsLars LochstoerSara LowesHanno LustigGary LynJeremy MagruderNadya MalenkoMichel MaréchalArnaud MaurelIsaac MbitiDavid McKenzieShaun McRaeAtif MianDaniel MillimetGiordano MionSidharth MoktanJack MountjoyNathaniel NelighSam NorrisMartin NybomStephen D. O’ConnellAndrey OrdinGuillermo OrdoñezChristopher PalmerJuan PantanoSahar ParsaToan PhanJoseph PriceJeffrey PrinceSimon QuinnAlex Rees-JonesMarkus ReisingerJean-Marc RobinBaxter RobinsonAndrés Rodríguez-ClareEvan RoseJonathan RothAdam SacarnyBernard SalaniéThomas SampsonClara SantamariaManuel SantosHeather SarsonsAlp SimsekAbhijeet SinghMattie TomaAleh TsyvinskiMatthew TurnerSergio UrzúaFelipe Valencia CaicedoStijn Van NieuwerburghDimitri VayanosEwout VerriestJonathan VogelChristian vom LehnOlivier WangMelanie WassermanMark WatsonJonathan WeigelJaya WenMirko WiederholtKevin WilliamsMilena WittwerVincent YaoStephen YeapleNoam YuchtmanAriel Zetlin-JonesAnthony ZhangSongfa ZhongSeth ZimmermanGabriel Zucman Previous articleNext article DetailsFiguresReferencesCited by Journal of Political Economy Volume 130, Number 11November 2022 Article DOIhttps://doi.org/10.1086/723188 Views: 501Total views on this site © 2022 The University of Chicago. All rights reserved.PDF download Crossref reports no articles citing this article.